IMPLEMENTASI STRATEGI PEMBELAJARAN AKTIF DALAM MENINGKATKAN PRESTASI BELAJAR AKIDAH AKHLAK PESERTA DIDIK MA NURUL FATTAH MARTAPURA TAHUN PELAJARAN 2023/2024 - Juniko Pratama; Suci Hartati (UNISAN JURNAL, 2024)
This research aims to explore the implementation of active learning strategies in increasing students’ understanding of the concept of moral beliefs at MA Nurul Fattah Martapura. The research method used is qualitative with a case study approach. The research participants consisted of two teachers and eighteen students of class XI MA Nurul Fattah Martapura. Data was collected through observation, interviews and document analysis. The research results show that the implementation of active learning strategies at MA Nurul Fattah Martapura consists of planning interesting learning, implementing learning that involves student interaction, and continuous learning evaluation. Implementation of this strategy has a positive impact on students’ understanding of the concept of moral beliefs, student involvement in learning, and development of students’ skills. Supporting factors for implementing this strategy include the availability of learning resources, support from the madrasa head, teacher commitment, and student involvement. However, there are also inhibiting factors such as limited time, resources, teacher skills, and curriculum incompatibility. Therefore, it is recommended that teachers continue to develop skills and knowledge in designing and implementing active learning, as well as for related parties at MA Nurul Fattah Martapura to provide more support in developing active learning strategies.